2006
DOI: 10.1515/hf.2006.099
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical investigation on phenolic deposits in the vessels of afzelia (Afzelia spp.) and merbau (Intsia spp.) heartwood

Abstract: The topochemical distribution of phenolic deposits in the vessels of afzelia (Afzelia spp.) and merbau (Intsia spp.) heartwood was investigated by means of cellular UV microspectrophotometry (UMSP) to characterise the chemical composition and synthesis by pit membraneassociated enzymes. UV absorbance spectra of the deposits attached to the vessel walls of merbau are characterised by a distinct maximum at a wavelength of 368 nm representing the UV absorbance of pure robinetin (C 15 H 10 O 7 ). Deposits in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…This spectral behaviour can be explained by the presence of chromophoric groups, for example, conjugated double bonds. The higher degree of conjugation stabilises p-p* transitions resulting in absorbance bands shifted to higher wavelengths (Goldschmid 1971) that can be detected by UV microspectrophotometry (Koch et al 2006). Against this, the spectra of extractives in the tissue of NMM-treated B. insigne were characterised by additional maxima in the range of 244-248 nm (Fig.…”
Section: Detection Of Nmm With Cellular Uv Microspectrophotometrymentioning
confidence: 96%
See 1 more Smart Citation
“…This spectral behaviour can be explained by the presence of chromophoric groups, for example, conjugated double bonds. The higher degree of conjugation stabilises p-p* transitions resulting in absorbance bands shifted to higher wavelengths (Goldschmid 1971) that can be detected by UV microspectrophotometry (Koch et al 2006). Against this, the spectra of extractives in the tissue of NMM-treated B. insigne were characterised by additional maxima in the range of 244-248 nm (Fig.…”
Section: Detection Of Nmm With Cellular Uv Microspectrophotometrymentioning
confidence: 96%
“…Note the higher deposition of NMM in cell lumens of B. ceiba; Tissues of axial parenchyma in B. ceiba (c) and B. insigne (f) treated with 20 % ML with extractives (tannins) deposited in cell lumens characterised by high absorbance intensities of 0.68-1.00. Size of UV pictures: a 57.50 9 39.00 lm = 36,267 pixels or measuring points; b 39.50 9 30.25 lm = 19,398 pixels or measuring points; c 60.75 9 55.00 lm = 53,924 pixels or measuring points; d 51.00 9 45.50 lm = 37,515 pixels or measuring points; e 43.50 9 42.00 lm = 29,575 pixels or measuring points; f 63.00 9 35.25 lm = 35,926 pixels or measuring points conglomerations of high absorbance values (abs 280nm 0.68-1.00) compared with the surrounding cell wall tissue (Koch et al 2006). The impregnation of NMM into the different morphological regions of B. ceiba and B. insigne wood tissue was (basically) confirmed by the analyses of point measurement absorbance spectra, which are shown in Figs.…”
Section: Detection Of Nmm With Cellular Uv Microspectrophotometrymentioning
confidence: 99%
“…Koch et al (2006) found pure Robinetin in heartwood vessels of Intsia spp. Differing from observation, the absorbance spectra indicate that, in the heartwood of Robinia, these flavonoids are not present in their pure form (Fig.…”
Section: Juvenile Woodmentioning
confidence: 94%
“…Extractions were carried out with acetone/water (9:1) and methanol/-water (3:1) at 60 °C under constant pressure at 100 atm and a static equilibration treatment of 5 min. according to Koch et al (2006).…”
Section: Chemical Analysis Of Heartwood Extractivesmentioning
confidence: 99%